Kinerja Birokrasi Pemerintah dalam Meningkatkan Pelayanan Masyarakat dengan Aplikasi Quick Respone dan WEB Di Kantor Kelurahan Kalisegoro Kecamatan Gunungpati Kota Semarang - Widayat, Aditya Putra; Munandar, Moh. Aris; Sumarto, Slamet (Unnes Political Science Journal, 2017)
The development of technology in particular telecommunication multimedia and information technology when itâs going to change the order of the organization and social relationships. Change to the goverment a democratic, transparent and accountable are starting to be done to good governance or good government. Issues that are examined in this study is (1) How the utilization of the aplication of the Quick Response and WEB by village goverment KalisegorO the district Gunungpati city of Semarang? (2) How the quality of public complaints in complaint to the village Kalisegoro thr district Gunungpati city of Semarang? (3) How the performance of the village Kalisegoro the district Gunungpati city of Semarang to provide service to the public after the application of the Quick Response and WEB? As a result of this study is the utilization of the application of the Quick Response and WEB in the village Kalisegoro aims to bring convenience to people and exellent service conductes by the village to the public. The quality of the complaint the community through the Quick Response and WEB is still low, due the factors of human resources some communities are still low. Performance af the village Kalisegoro to make the application of the Quick Response and WEB, to the villages that have age in over 45 year still be hired and given training in using the application. Good advice presented in this study is the need for improvements to the implementation of the application Quick Response and WEB in the village Kalisegoro, to the addition of officer (admin) which handles complaints public, the addition of the computer for more data capacity by the application of the Quick Respone and WEB. There needs to be officials of the violence and thhoroughly to the village Kalisegoro as application of the Quick Respone and WEB to complaints given by the standards provided by the village Kalisegoro.